Językowy obraz Żyda według zbioru Leona Węglińskiego Hôrkij śmich. Skazki i obrazki z żytia w Hałyczyni - Ilchyna, Olha (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
This text is an attempt at analysing the linguistic image of a J ew on the basis of Hôrkij śmich by a little-known Ukrainian poet Leon Węgliński. According to researchers, every language has a specific interpretation of reality which is expressed in a unique view and perception of the world. This article, through a thorough analysis of the vocabulary, grammar structures and descriptions, shows the images of a J ew in the nineteenth century: his identity, character traits and daily functioning. The material gathered for the study presents a definitely negative image of a J ew.